IMPLEMENTING THREE STEP INTERVIEW IN TEACHING SPEAKING - Olyvia Revalita Candraloka (Universitas Islam Nahdlatul Ulama Jepara, 2016)
Speaking plays an important role in English learning. Since some students speak actively in classroom, it is high time for teachers to apply one of cooperative learning methods in class. The main purpose of this article is to describe methods and the results of a work designed to analyze the implementation of Three Step Interview in teaching speaking. This article begins with the overview teaching speaking include problems in teaching speaking, and the activities of teaching speaking. It also explains the concept of Three Step Interview technique and the implementation of the technique.